Mãe d’água: uma abordagem mitológica para a (re)educação com dança no cárcere feminino em Belém do Pará - COSTA, Halana Monique Figueira da (2018)
This work intends to describe the teaching process of dance in a female prison in Belem do Pará inspired in the Amazon mythology of “Mãe d’Água”. Aiming to enhance the Amazonian culture, interfere with resocialization process, raise the self-confidence of women, emphasizing the body participatory social instrument in the construction of knowledge, supported by ethnoscenologics studies and semiotics conversion when the myth is presented as teaching methodology. I expose about the reality of women's detention Female “Centro de Reeducação Feminino - CRF” (Center of Reeducation - FCR) and the meeting with dance. For practical methodological development, I use the application of different physical techniques as somatic education, folk dance from Pará and improvisation, the teachinglearning process of dance doesn’t intends a ready esthetical result, the process frequented by the body and the provided experiences are fundamental in the research, until the moment that the inmate feels the urge to create, confident of herself.